2008
DOI: 10.1590/s1516-89132008000700028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tripanosomicide benznidazole (Rochagan®) on the biodistribution of sodium pertechnetate (Na99mTcO4) in Wistar rats

Abstract: Benznidazole, a drug with specific anti-Trypanosoma cruzi activity, is used in the treatment of Chagas' disease. The radiopharmaceutical sodium pertechnetate (Na99mTcO4) is used to obtain diagnostic images of the stomach, thyroid, parathyroids, salivary glands, brain and in the study of esophageal reflux and blood flow. This study aimed at evaluating in vivo the influence of benznidazole treatment on the sodium pertechnetate biodistribution in Wistar rats. The percentage of radioactivity per gram (%ATI/g) of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Several experimental models have been used to evaluate the properties of synthetic and natural drugs [6][7][8] . The biodistribution of radiopharmaceuticals in the animal organism can be changed with concomitant use of drugs natural and/or synthetic, certain diets, parasitic infections, the use of cigarettes and surgery, as demonstrated in studies described by Araújo-Filho et al 15 and Rêgo et al 16 .…”
Section: Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental models have been used to evaluate the properties of synthetic and natural drugs [6][7][8] . The biodistribution of radiopharmaceuticals in the animal organism can be changed with concomitant use of drugs natural and/or synthetic, certain diets, parasitic infections, the use of cigarettes and surgery, as demonstrated in studies described by Araújo-Filho et al 15 and Rêgo et al 16 .…”
Section: Organsmentioning
confidence: 99%
“…In the applications in nuclear medicine diagnostic, the isotope technetium-99m ( 99m Tc) has preferred choice. Technetium-99m may bind to different substrates or ligands, resulting radiopharmaceuticals with affinity for different organs, systems or receptors in the body [6][7][8] . Technetium-99m in the form of sodium pertechnetate, or labeled with other structures, such as sodium phytate ( 99m Tc-sodium phytate) or dimercaptosuccinic acid ( 99m Tc-DMSA) are the most frequently used radiopharmaceuticals in nuclear medicine 9 .…”
mentioning
confidence: 99%
“…The biological behavior of radiopharmaceuticals used for diagnosis in nuclear medicine is well established in the scientific literature. There is evidence that radiopharmaceutical biodistribution may be altered by infectious diseases, procedures, cigarette smoking, surgery, food or natural and synthetic drugs [20][21][22][23][24] . The present study demonstrated that the uptake of Na 99m TcO 4 was not altered…”
Section: Discussionmentioning
confidence: 99%